2017
DOI: 10.1038/s41598-017-08519-4
|View full text |Cite
|
Sign up to set email alerts
|

A complex of Neuroplastin and Plasma Membrane Ca2+ ATPase controls T cell activation

Abstract: The outcome of T cell activation is determined by mechanisms that balance Ca2+ influx and clearance. Here we report that murine CD4 T cells lacking Neuroplastin (Nptn −/−), an immunoglobulin superfamily protein, display elevated cytosolic Ca2+ and impaired post-stimulation Ca2+ clearance, along with increased nuclear levels of NFAT transcription factor and enhanced T cell receptor-induced cytokine production. On the molecular level, we identified plasma membrane Ca2+ ATPases (PMCAs) as the main interaction par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 48 publications
6
67
0
Order By: Relevance
“…In addition, an additional phospholipid-binding domain that contains about 40 predominantly basic amino acids exists in the first cytosolic loop of mammalian PMCAs, providing the second binding site for acidic phospholipids 17 . Recently, two immunoglobulin (Ig) superfamily proteins, neuroplastin (NPTN) and basigin (BASI), were identified as previously unrecognized obligatory subunits of PMCAs and essential for the efficient control of the PMCA-mediated Ca 2+ clearance 10 , 18 , 19 . However, detailed structural information is unavailable for NPTN- or BASI-bound PMCAs and the molecular mechanism underlying the active effect of the subunits on PMCAs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an additional phospholipid-binding domain that contains about 40 predominantly basic amino acids exists in the first cytosolic loop of mammalian PMCAs, providing the second binding site for acidic phospholipids 17 . Recently, two immunoglobulin (Ig) superfamily proteins, neuroplastin (NPTN) and basigin (BASI), were identified as previously unrecognized obligatory subunits of PMCAs and essential for the efficient control of the PMCA-mediated Ca 2+ clearance 10 , 18 , 19 . However, detailed structural information is unavailable for NPTN- or BASI-bound PMCAs and the molecular mechanism underlying the active effect of the subunits on PMCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this proposition, it has been reported recently that TRAF6 efficiently binds to and regulates the stability of PSD-95 as a necessary step for the plasticity of hippocampal mature spines (Ma et al, 2017). Alternatively, neuroplastin could also change its predilection for interaction partners in young neurons as it becomes an essential subunit for the four paralogs in mature neurons (Bhattacharya et al, 2017;Herrera-Molina et al, 2017;Korthals et al, 2017;Schmidt et al, 2017;Gong et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Very recently, it has been discovered that neuroplastin interacts with all four plasma membrane Ca 2+ ATPases (PMCA1-4) stabilizing the surface expression of these pumps (Bhattacharya et al, 2017;Herrera-Molina et al, 2017;Korthals et al, 2017;Schmidt et al, 2017;Gong et al, 2018). Thus, we addressed the obvious question whether TRAF6 or neuroplastin require PMCA to promote dendritic protrusion density.…”
Section: Traf6 Confers the Spinogenetic Capacity To Neuroplastinmentioning
confidence: 99%
“…More recently, Schmidt et al [11] identified Nptn as a novel subunit of native plasma membrane Ca 2+ -ATPases (PMCAs). In addition, Korthals et al [12] reported that PMCA levels were dramatically reduced and Ca 2+ levels were significantly increased in internal stores of Nptn À/À T cells. These reports suggest that Nptn may be a key regulator of intracellular Ca 2+ concentration, through which it may influence behaviors and brain function in rodents.…”
Section: Introductionmentioning
confidence: 99%